2015
DOI: 10.3329/bpj.v18i1.23521
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetics in combination with hydroxychloroquine improve antioxidant and hepatoprotective activities in alloxan-induced diabetic rats

Abstract: Hyperglycemia exerts toxic effects on the pancreatic β-cells. This study investigated the hypothesis that the antidiabetic drugs glibenclamide and metformin, in combination with hydroxychloroquine (HCQ) offer additional protection for the pancreas against oxidative stress and produce hepatoprotective effect in alloxan-induced diabetic rats. Diabetes was induced in male Long-Evans rats by a single dose of alloxan (120 mg/kg; i.p.). Different groups of diabetic animals were treated with glibenclamide (10 mg/70 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The enzymes SGPT, a cytosolic enzyme primarily present in the liver and SGOT, a mitochondrial enzyme released from heart, liver, skeletal muscle and kidney are the most sensitive markers employed in the diagnosis of liver diseases. These enzymes leak through the liver cell membrane into the blood circulation while liver cells are injured or died, and serum levels become increase (Zannah et al, 2015). It is concluded that diabetes is associated with hepatocellular damage (Thenmohzi and Subramanian, 2009) as diabetic rats show a significant increase of these markers.…”
Section: Effects On Catalase Enzyme Activitymentioning
confidence: 99%
“…The enzymes SGPT, a cytosolic enzyme primarily present in the liver and SGOT, a mitochondrial enzyme released from heart, liver, skeletal muscle and kidney are the most sensitive markers employed in the diagnosis of liver diseases. These enzymes leak through the liver cell membrane into the blood circulation while liver cells are injured or died, and serum levels become increase (Zannah et al, 2015). It is concluded that diabetes is associated with hepatocellular damage (Thenmohzi and Subramanian, 2009) as diabetic rats show a significant increase of these markers.…”
Section: Effects On Catalase Enzyme Activitymentioning
confidence: 99%
“…Group C Diabetic rats treated with metformin (daily administered 850 mg/70 kg b.w.) [18]. Group D Diabetic rats treated with β-carotene (daily administered 10 mg/70 kg b.w.)…”
Section: Experimental Designmentioning
confidence: 99%
“…The present long term studies on the combination therapy of BME with metformin provided some light on the beneficial effects like antioxidant and hepatoprotective actions in normal and AIDRs. IP injection of freshly prepared alloxan monohydrate (110 mg/kg BW) solution was used to induce diabetes (BGL ≥ 11.1 mmol/l) among the 16 hours fasted rats (Zannah et al, 2015). Alloxan selectively kills the pancreatic -cells because it preferentially accumulates in cells through uptake via the GLUT2 glucose transporter.…”
Section: Effects On Antioxidant Enzyme Activitiesmentioning
confidence: 99%
“…Both of these enzymes are the most sensitive markers employed in the diagnosis of liver diseases. When liver cells are injured or died, these enzymes can leak through the liver cell membrane into the blood circulation and serum levels become increase (Zannah et al, 2015). As diabetic rats show a significant increase in these liver markers so it is conclusive that diabetes is associated with hepatocellular damage (Thenmohzi and Subramanian, 2009).…”
Section: Effects On Antioxidant Enzyme Activitiesmentioning
confidence: 99%